2007
DOI: 10.1080/13557850601002171
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Pediatric injury patterns by age and ethnic groups in Israel

Abstract: The findings of this study show that there is variability in external cause of injury and severity by age and ethnic group. Falls were most frequent among young children and burns among non-Jews. Non-Jewish children in SES clusters 1-4 are at high risk for falls from height, suggesting intervention and prevention activities should be directed in this direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
3
13
1
1
Order By: Relevance
“…Comparison between EBI and FSUBI demonstrated greater risk of violence-related injury hospitalization among EBI. The results are consistent with numerous studies that found higher risk of violence and intentional injuries among ethnic minorities compared to the general population (Abdel-Rahman, Siman-Tov, and Peleg 2013;Cercarelli and Knuiman 2002;Chatman et al 1991;Cubbin and Smith 2002;Demetriades et al 1998;Farchi et al 2005;Friedman and Forst 2008;Goral et al 2006;Johnson, Sullivan, and Grossman 1999;Rozenfeld and Peleg 2009;Sampson, Morenoff, and Raudenbush 2005;Savitsky et al 2007;Stirbu et al 2006; The Gertner Institute for Epidemiology and Health policy research 2011; WHO 2008; WHO Europe 2009). The different compositions of socioeconomic characteristics between the ethnic groups may possibly explain these observed inequalities in violence injury.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Comparison between EBI and FSUBI demonstrated greater risk of violence-related injury hospitalization among EBI. The results are consistent with numerous studies that found higher risk of violence and intentional injuries among ethnic minorities compared to the general population (Abdel-Rahman, Siman-Tov, and Peleg 2013;Cercarelli and Knuiman 2002;Chatman et al 1991;Cubbin and Smith 2002;Demetriades et al 1998;Farchi et al 2005;Friedman and Forst 2008;Goral et al 2006;Johnson, Sullivan, and Grossman 1999;Rozenfeld and Peleg 2009;Sampson, Morenoff, and Raudenbush 2005;Savitsky et al 2007;Stirbu et al 2006; The Gertner Institute for Epidemiology and Health policy research 2011; WHO 2008; WHO Europe 2009). The different compositions of socioeconomic characteristics between the ethnic groups may possibly explain these observed inequalities in violence injury.…”
Section: Discussionsupporting
confidence: 93%
“…Contrary to several scientific studies which identified a greater risk of RTIs among ethnic minorities than their major counterparts, our study found the opposite (Abdel-Rahman, Siman-Tov, and Peleg 2013; Cubbin and Smith 2002;Farchi et al 2005;Johnson, Sullivan, and Grossman 1999;Savitsky et al 2007;Steinbach et al 2010Steinbach et al , 2007Stirbu et al 2006;WHO Europe 2009;WHO 2008). Given that minority ethnic status is often correlated with both individual and area deprivation, it is perhaps expected that minorities are often at higher risk to RTI.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The fact that most of the Arab population has a lower SES may determine the existence of these environments and the exposure of Arab children to hazardous conditions, thus explaining the higher rates of injury (Dowswell & Towner, 2002;Ivancovsky & Kislev, 2011;Klein, Oppenheim, Ivancovsky, Silbinger, & Danon, 2012). Even after adjusting for SES, which decreased the difference between the two groups the proportion of severe injuries among Arab children was higher than among Jewish children (Savitsky, Aharonson-Daniel, Giveon, Group, & Peleg, 2007).…”
Section: Unintentional Injuries Among Arab and Jewish Children In Israelmentioning
confidence: 98%
“…A large literature links socio-economic disadvantage with increased risk of child pedestrian injury (Laflamme, Hasselberg, andBurrows 2010, Laflamme andDiderichsen 2000). Increasingly, a number of studies in a range of countries have also suggested ethnic differences in child pedestrian injury risk, with most (Abdalla 2002, Campos-Outcalt et al 2002, Harrop et al 2007, Rivara and Barber 1985, Savitsky 2007, Stirbu 2006, Abdel-Rahman et al 2013), but not all, (Al-Madani and Al-Janahi 2006) studies reporting that minority ethnic groups are at greater risk than their majority counterparts. Given that minority ethnic status is often correlated with both individual and area deprivation, it is perhaps unsurprising that minority children are often at higher risk.…”
Section: Introductionmentioning
confidence: 99%